2019
DOI: 10.29244/cb.4.3.13-22
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial Activity and Phytochemical Analysis of <i>Geranium homeanum</i> Turez Leaves

Abstract: Geranium homeanum Turez is a herbaceous plant used as an empirical medicine. This research was carried out to test the antibacterial activity and determine minimum inhibition concentration (MIC) to Staphylococcus aureus and Pseudomonas aeruginosa with agar diffution method and phytochemical analysis of geranium leaves  by Harbone method. The young and old geranium leaves were blended then filtrated. The obtained filtrate was divided into two parts, one part heated by autoclave and the other was unheated. Each … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
7

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 0 publications
0
10
0
7
Order By: Relevance
“…It was reported that phenol can interfere with the growth of Staphylococcus aureus through their acidic properties which allows them todenaturate proteins and can damage cell membranes 25 . Triterpenoids act on the cell wall by damaging the wall structure and can interfere with active transport in the cytoplasm of bacteria 26 .…”
Section: Resultsmentioning
confidence: 99%
“…It was reported that phenol can interfere with the growth of Staphylococcus aureus through their acidic properties which allows them todenaturate proteins and can damage cell membranes 25 . Triterpenoids act on the cell wall by damaging the wall structure and can interfere with active transport in the cytoplasm of bacteria 26 .…”
Section: Resultsmentioning
confidence: 99%
“…Triterpenoids dissolve readily in polar solvents, including water, owing to their composition. Geraniums' triterpene content has also been reported to be antibacterial 24 .…”
Section: Discussionmentioning
confidence: 99%
“…The terpenoid compounds action mechanism is by damaging the outer membrane, inner membrane and can also interact with membrane proteins with the help of alkaloids by inhibiting the formation of enzymes (esterase, DNA-, RNA-polymerase), inhibiting cell respiration. 12 produces an average inhibition diameter of 15.5 mm. The average inhibition diameter owned by amoxicillin is quite strong.…”
Section: Discussionmentioning
confidence: 99%